Dampak Layanan Bimbingan Klasikal Terhadap Pencegahan Perilaku Bullying pada Siswa SMPN 4 Tambang - Donal Donal; Dea Safitri; Fajri Rivel; Nur Najhiha Izzaty (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the impact of classical guidance services in preventing bullying behavior in students. This study uses a qualitative approach with the type of action research. The sample consisted of 88 students in grades VII and VIII at SMPN 4 Tambang who were selected through purposive sampling techniques based on the highest bullying behavior scores. Data were obtained through observation, interviews, and documentation studies. The results of the study indicate that classical guidance services delivered communicatively with the help of PowerPoint presentation media and supporting videos about bullying behavior, are able to improve students' understanding of the forms of bullying, as well as foster an attitude of empathy and mutual respect. In addition, students' active participation in discussions and reflections shows a positive change in attitude. This service has proven effective as a preventive effort in creating a safe and bullying-free school environment.